Les Déterminants de l’Indépendance De l’Auditeur - Najah, El Azhary; Omar, Taouab (European Scientific Journal, ESJ, 2016)
The financial failures and economic crisis that took place in many nations of the world didn’t exclude Morocco from countries that must reinforce governance mechanisms so as to be more performant. In fact, the effort must focus not only on the creation of governing authorities inside organizations, but also by preparing a good framework enabling them to exercise their role in the best conditions of impartiality and independence. It’s through this vision that this article attempts to present conspicuously the measures that have to be taken into consideration for more realistic independence of two governing authorities, namely, the internal audit and legal audit.